Evaluating the impact of the Earthkeepers Earth education program on children's ecological understandings, values and attitudes, and behaviour in Cyprus - Manoli, Constantinos C.; Johnson, Bruce; Hadjichambis, Andreas Ch; Paraskeva-Hadjichambi, Demetra; Georgiou, Yiannis; Ioannou, Hara (My University, 2014)
The recent educational reform in Cyprus moved education about sustainability to the forefront of environmental learning. The present study examines the impact of an earth education program, Earthkeepers, on children's ecological understandings, environmental values and attitudes, and behaviour. The program was implemented during two consecutive years with 491 4th to 7th graders from nine different schools in Cyprus. Quantitative data were collected using individual concept, attitude and behaviour questionnaires, and a satisfaction survey. Qualitative data were collected using individual semi-structured interviews with twelve students and nine teachers from six different schools. Data analysis showed gains in students' understanding as well as significant changes towards more pro-environmental values, attitudes and behaviour. Interviews confirmed the quantitative results and verified students' behaviour.
Keywords: Earth education; Ecological understandings; Environmental attitudes; Environmental behaviour; Environmental values; Sustainability